Gruber o širjenju plinov v vakuum - Južnič, Stanislav (Vakuumist, 2004)
The first observation of the cooling of gases during their expansion in vacuum was described. The share our Slovene scientist Gruber gave to the early research was acknowledged with pride. We concluded our story with the usuable explanation of the effect in the works of Joule and Thomson, and with the technological and industrial use of the Joule expansion in the early race for the condensation of the gases previously considered permanent.
Keywords: Gruber, Gabrijel, 1740-1805; plini; vakuum; zgodovinski pregledi